Pengaruh antara Kepemimpinan Kepala Sekolah dan Motivasi Kerja terhadap Kinerja Guru Sekolah Minggu Buddha (SMB) Chong-De Se Sumatera Utara - Johan Johan; Muljadi Muljadi; Isomudin Isomudin (Institut Nalanda, 2024)
Performance of the Chong-De Buddhist Sunday School (SMB) teachers in North Sumatra. This research uses multiple regression analysis. In this study using a sample using probability sampling technique, with a total sample of 86 respondents. This research uses primary data, data is collected by distributing questionnaires to respondents via google form which is tested with SPSS 20.0 for Windows. The results showed that the principal's leadership had a positive effect on the performance of SMB Chong-De teachers throughout North Sumatra with a correlation coefficient score (ry1 = 0.613) and a score determination coefficient (r2y1 = 0.375). Work motivation has a positive effect on the performance of SMB Chong-De teachers in North Sumatra with a correlation coefficient score (ry2 = 0.762) and a determination coefficient score (r2y2 = 0.581). Principal leadership and work motivation have a positive and significant effect on the performance of Chong-De High School teachers in North Sumatra with a correlation coefficient score (ry1,2 = 0.835) and a coefficient of determination score (r2y1,2 = 0.698). Regression equation: 1.2 = 49.013 + 0.835X1 + 0.698X2. So for optimizing teacher performance, a policy or regulation is needed to improve school principal leadership and work motivation.